Practical application of an extended container transport problem for the transport of bulk cargo - Krčmář, Pavel (2010)
The thesis concerning practical application of a container transport problem in a case of a company trading kitchen appliances, concretely optimizing costs of the transport of goods from three warehouses to five stores with four different types of cars.